The suitability of technology, organization and environment (TOE) and socio technical system (STS) for assessing IT hardware support services (ITHS) model. - Azham, Ahmad; Zainuddin, Othman; Ruzaini, Abdullah Arshah; Adzhar, Kamaludin (IOP Publishing, 2021)
IT support services are the crucial part in daily business operation services in any organization. Special attention is needed, especially in managing users or client satisfaction when using the IT services to address the user's problem or request IT hardware issues. Service quality (SQ) dimension is used to measure the effectiveness in delivering IT service support hardware to users. To strengthen the elements of the ITHS (IT Hardware Support Services), information system theories (IS) are used to harmonize the IT environment especially on the service support related to the IT hardware component. Two such theories taken from the IS environment are: Technology, Organization and Environment (TOE) and Social Technical System (STS). In this model, discussion is on the suitability of the above theories to assess ITHS, ability to achieve the service quality that reflect back to the users, client, and organization in achieving the service performance based on the SERVQUAL dimension.